A study on the behavior of laminated and sandwich composite plates using a layerwise theory - Venâncio, M. A. S. (2016)
The numerical study of structures constituted from composite materials, regardless the underlying shear deformation theory used may be framed into an equivalent single-layer or a layerwise methodology. The adoption of one of these approaches is mainly ruled by the detail one needs to put in the description of the deformation kinematics and on the subsequent description of other relevant quantities such as stresses or frequencies. Being important to address both qualitative and quantitatively the influence of different parameters involved in the models and materials used to represent a structure, it is also relevant to understand how layerwise theories can predict its static and dynamic response. These different issues may be addressed by carrying out parametric studies to characterize the influence of specific parameters on the mechanical performance of sandwich and laminated composite plates. To this purpose a layerwise theory based on the first order shear deformation theory, is considered, and a set of different test cases are analyzed in light of this approach, providing results which may also be useful for later comparison purposes.